A high degree of enhancement of strength of sputter deposited Al/Al2O3 multilayers upon post annealing. (15th August 2015) - Goswami, R.; Pande, C.S.; Bernstein, N.; Johannes, M.D.; Baker, C.; Villalobos, G.
Abstract: We report here an order of magnitude enhancement of strength of sputter deposited Al/Al2 O3 multilayers after annealing. The increase in strength is shown to be mostly associated with the precipitation of extremely fine γ -Al2 O3, 5–10 nm in diameter, in Al layers. This provides a new method of achieving high strength in Al/Al2 O3 multilayers that cannot be explained by the Koehler effect or modified Hall–Petch, which will lead to the growth and development of new generation of Al/Al2 O3 multilayers. We also examine the fracture behavior of the post annealed Al/Al2 O3 multilayered composites with TEM and density functional theory (DFT) simulations. DFT showed that the multilayers are not likely to delaminate at the Al/Al2 O3 interface, consistent with the experimental observations. The simulations are also used to determine elastic constants for the γ -Al2 O3 phase and to calculate a driving force for O transport from the γ -Al2 O3 to the Al layers. The formation of these precipitates is consistent with DFT calculations, which predict an energetic driving force for the dissolution of O atoms from the γ -Al2 O3 layers into the Al layers.